Maurin, E. (2009), "Le peur du dèclassement: Une sociologie des récessions", Éditions du Seuil / La République des Idées, París. - FERNÁNDEZ RODRÍGUEZ, Carlos Jesús; HEIKKILÄ, Riie (Cuadernos de Relaciones Laborales, 2010)
Sin resumen